Caracterização Petrográfica e Geoquímica da Parte Leste do Granito Europa, Distrito Mineiro de Pitinga, AM - PRADO, MAURÍCIO; MIRRAS FERRON, JOSÉ TADEU MAXIMINO; DE LIMA, EVANDRO FERNANDES; BASTOS NETO, ARTUR CEZAR; PEREIRA, VITOR PAULO; RIGON MINUZZI, ORLANDO RENATO; PIEROSAN, RONALDO (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> The important mineral deposits of the Pitinga Mine, in the Amazonian region are related to A-type granites intruded in the Iricoumé Group. The Europa granite is one of these A-type rocks, intruded in the Iricoumé Group, which is represented by subaerial vulcanoclastic rocks (crystal-rich ignimbrites, thin massive tuffs and siltic tufaceous arenites) and minor hipabissal rhyolites. The volcanic rocks were probably generated in a caldera environment. The Europa granite is an alkali-feldspar peralkaline granite (hipersolvus) without genetic relationship with to the volcanic rocks of the Iricoumé Group, but it could have been generated during the resurgence stages. The petrographic and geochemical data attest that fractional crystallization process was the principal mechanism during the crystallization, which led to the generation of two different granitic facies. The Nb soil anomalies overprinted on the more differentiated facies are related to the astrophillite weathering.